Ocean Remedies in Homoeopathy: A Study of Subconscious Themes and Clinical Expression (Homoeopathy for All, 2026)
Ocean-derived remedies represent  a distinctive and conceptually  significant group within  homoeopathic materia medica,  prepared from a variety of marine  sources including organisms,  minerals, and seawater. These  remedies are closely associated with  deep-rooted psychological patterns  that reflect fundamental dimensions  of human experience. They  commonly express core polarities  such as connection versus isolation,  vulnerability versus protection and  sensitivity versus withdrawal. Such  contrasting tendencies offer valuable  insight into subconscious conflicts,  primitive survival responses and  their manifestation in clinical  conditions.
Keywords: Ocean remedies; Homoeopathy; Subconscious patterns; Psychosomatic disorders; Marine medicines; Materia medica